2017
DOI: 10.1007/s00420-017-1230-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of resistance training in women with chronic computer-related neck pain: a randomized controlled study

Abstract: The study was qualified and registered in the Chinese Clinical Trial Registry as ChiCTR-TRC-12002723.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(81 citation statements)
references
References 42 publications
2
76
1
1
Order By: Relevance
“…In the present study, the control group statistically differed only from the CnT group in the shoulder-neck mobility after the intervention, which reached the greater differences from baseline, although without statistical differences compared with the ET intervention (Zumba fitness ® isolated). In this sense, different studies in adults have reported improvements in this physical fitness variable after a strength training program, but mostly they were focused on a physical rehabilitation program [40,41]. As the effect of the strength training program was not evaluated separately, it is not possible to know which program produced the improvements in this variable.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the control group statistically differed only from the CnT group in the shoulder-neck mobility after the intervention, which reached the greater differences from baseline, although without statistical differences compared with the ET intervention (Zumba fitness ® isolated). In this sense, different studies in adults have reported improvements in this physical fitness variable after a strength training program, but mostly they were focused on a physical rehabilitation program [40,41]. As the effect of the strength training program was not evaluated separately, it is not possible to know which program produced the improvements in this variable.…”
Section: Discussionmentioning
confidence: 99%
“…All these patients had a long duration (more than 1 year) complaint of classical TN according to the International Classification of Headache Disorders criteria (third edition) [ 19 ] and had high-resolution imaging to exclude secondary causes of TN. Visual analogue scale (VAS) [ 20 ] was used to assess pain intensity in the TN patients. All patients were measured during a painful attack and on medications.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple reports of the same trial were collated for Waling et al, 2002 [48-50], Bobos PLOS ONE et al, 2016 [51,52], Ylinen et al, 2007 [53-56], and Chiu et al, 2005 [57, 58]. Data extraction was completed for 26 trials [13,14,49,51,54,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. https://doi.org/10.1371/journal.pone.0234511.g001 Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 2 provides a brief description of exercise training programmes and dosage. ET was delivered via supervised sessions [13,49,54,57,60,65,68,70,73,75,76], a home exercise programme [63,69,74] or a combination of the two [14,51,59,61,62,64,66,67,71,72,77,78], using a range of equipment including resistance bands [51,54,62,65,74,77], biofeedback pressure units [13,51,57,59,60,63,64,69,70,[72][73][74][75], dumbbells [14,54,61,…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation